Legal Framework for Addressing Cybercrime Threats in Strengthening Indonesia’s National Defense and Security - Shobri, Taufiq; Yusgiantoro, Purnomo; Navalino, Djoko Andreas; Sutanto, Sutanto (Faculty of Law Universitas Trunojoyo Madura, 2026)
This study aims to analyze the forms of cybercrime threats in Indonesia and examine the existing legal framework for addressing them. The study contributes to strengthening the legal perspective on cybercrime regulation by identifying weaknesses in current regulations and proposing improvements to support national cybersecurity governance. This research employs a normative legal research method using statutory, conceptual, and case approaches. Data were collected through a literature review of laws and regulations, academic journals, policy reports, and other relevant legal sources, and analyzed qualitatively. The findings indicate that cybercrime threats in Indonesia continue to grow in both scale and complexity, including phishing, ransomware, malware attacks, Distributed Denial of Service (DDoS), and data breaches targeting government institutions and financial sectors. Although Indonesia has enacted several regulations, such as the Electronic Information and Transactions Law and the Personal Data Protection Law, the regulatory framework remains fragmented and lacks comprehensive legal provisions governing national cybersecurity. The study concludes that strengthening the legal framework and institutional coordination is essential to improve cyber defense and national security. Therefore, this study recommends developing a comprehensive cybersecurity law, improving inter-agency coordination, and enhancing capacity in cybersecurity governance to effectively address cybercrime threats in Indonesia.